The implications of Apple's battle with the FBI. Issue 7 (July 2016) - Hack, Michael
Abstract : The recent high-profile clash between the FBI and Apple in the US has reopened a debate on privacy that has far-reaching implications that extend far beyond the semantic boundaries of the security and privacy models pursued by the technology sector. The recent high-profile clash between the FBI and Apple in the US has reopened a debate on privacy that has far-reaching implications. Alongside calling into question the rights of government in relation to whether there are legal precedents for forcing tech companies to grant access to code and data, the dispute has raised public awareness of digital privacy and civil rights issues. What's at stake is the point at which digital security ends and national security begins, argues Michael Hack of Ipswitch.